POVERTY AMONG TERTIARY INSTITUTION STUDENTS: A GENDER PERSPECTIVE (A STUDY OF NASARAWA STATE POLYTECHNIC LAFIA) - OJO, STEPHEN S.; AGARA, JUMMAI J.; POJWAN, MARTINA A. (IJRDO - Journal of Social Science and Humanities Research, 2016)
The quest to acquire higher education has greatly increased in recent time in Nigeria. Education is seen as a means of escaping from poverty and at the same time, poverty has also pose a challenge/limitation or hindered many from acquisition of qualitative education. In order to ascertain the influence of poverty in tertiary institutions, this study seeks to identify the prevalence of poverty among students generally with particular reference to Nasarawa State Polytechnic students, Lafia. The methodology adopted descriptive survey which involves the use of structured questionnaire for the collection of information on the level of total students’ consumption expenditure and other socio-economic characteristics, which might influence the occurrence of poverty in one way or the other. A sample of 120 respondents was selected using purposive sampling method and data collected were analyzed using descriptive statistics. The study reveals that there is prevalence of poverty among students of the polytechnic, and this affects more male students than female students which also influence their academic performance.